ANALYSIS OF FACTORS AFFECTING THE INCOME OF FISH TRADERS - Suseno. D.A.N.; Supriyadi. B; Nugraha. J.P.; Rahardjo. S; Suseno. D.N (MSJ : Majority Science Journal, 2024)
Research on factors that influence fish traders' income is still limited regarding business experience and business analysis carried out by fish traders. The importance of analyzing the factors that influence fish traders' income cannot be underestimated in the context of fisheries economics in increasing the per capita income of fish traders in Indonesia. Therefore, this research aims to analyze which factors have the most influence on fish traders' income, with the variables Capital (x1), Trading Time (x2), and Selling Time Allocation (x3). Determining respondents in the study used a purposive sampling method, namely fish traders in the Sedati District area, Sidoarjo. The number of respondents will be determined using the Slovin method, and the data obtained will be analyzed using the multiple linear analysis method. The data obtained were analyzed using the SPSS application and showed that the capital variable (x1) was proven to have a positive influence on fish income in the Sedati District area, with a t table value of 2,233 > 1.697 t count and a sig value = 0.033 < 0.05 so that Ha was accepted. The conclusion of this research is that the capital variable (x1) has a real influence on the income of fish earners in Sedati District. This research is useful for the community, especially fish traders, that sufficient capital is the most influential thing in obtaining income, because the greater the capital used, the greater the income obtained.